The Effect of Supervision of the Principal in Increasing Teacher Performance in SMA 1 Koto Besar Dharmasraya West Sumatra - Wakini Wakini; Jamilus Jamilus (BIRCU, 2021)
Supervision carried out by principals to improve teacher performance is an important thing to continue to improve. Because it will affect the performance of teachers in carrying out their duties. Supervision can be interpreted as a service business and assistance in the form of guidance from superiors, namely the principal, to school personnel such as teachers and other officers to become proficient in accordance with the development of science. The purpose of this study was to determine the role of the principal's supervisor in improving the performance of SMA 1 Koto Besar teachers. The research method used is correlational quantitative. The subject of the study was a teacher of SMA 1 Koto Besar, which amounted to 17 people. From the results of the study it was found that the average value of the principal's supervision was 82 in the good category, and the average teacher performance score was 87.5 in the very good category. From the results of hypothesis testing, the value of Sig. of 0.016 <0.05 with a magnitude of 43.7. So it can be concluded that there is a significant relationship between principal supervision and teacher performance at SMA Negeri 1 Koto Besar.